A polyacid catalyst for selective oxidation of aniline under visible light conditions based on {P4Mo6} crystal state and its application

By using a polyacid catalyst based on the crystalline state of {P4Mo6} under visible light conditions, the problem of high pressure and high temperature of the existing catalyst is solved, and the efficient and highly selective reaction of oxidizing aniline to azobenzene is achieved, and the catalyst has good cycle stability.

CN116196951BActive Publication Date: 2025-04-29BOHAI UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310023040.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-01-06
Publication Date
2025-04-29
Estimated Expiration
2043-01-06

AI Technical Summary

Technical Problem

Existing catalysts require high pressure and high temperature conditions when catalyzing the oxidation of aniline to azobenzene, and the use cost of precious metal nanocomposites is high.

Method used

The catalyst was synthesized by hydrothermal method under visible light conditions using a polyacid catalyst based on the crystalline state of {P4Mo6} for selective oxidation of aniline.

Benefits of technology

It is achieved efficient catalytic oxidation of aniline to azobenzene at room temperature without the need for photosensitizer, with a conversion rate of 97%, a selectivity of 96%, and the catalyst has high activity, structural stability and excellent recycling.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116196951B_ABST
    Figure CN116196951B_ABST
Patent Text Reader

Abstract

A polyoxometalate catalyst based on {P4Mo6} crystal for selectively oxidizing aniline under visible light conditions and its application. The molecular formula of the catalyst is as follows: (Hbiz)5{[Co(H2O)3][Co(H2O)2]2}{Co[Mo6O 12 (OH)3(PO4)(HPO4)3][Mo6O 12 (OH)3(PO4)2(HPO4)2]}·3H2O. Conditions for the catalytic oxidation of aniline selectively catalyzed by it: irradiated under a 300W xenon lamp, at room temperature, with the complex as the catalyst, 30% H2O2 with a mass concentration as the oxidant and Na2HSO3 under the condition of a mixed solvent of acetonitrile and acetic acid, irradiated by the xenon lamp for 12 h. Advantages: The preparation method is simple, raw materials are easily available, and the price is cheap. The catalyst has high activity and stability for selectively catalyzing the oxidation of aniline to azobenzene under visible light drive.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of catalyst preparation, and in particular to a polyacid catalyst based on {P4Mo6} crystal for selectively oxidizing aniline under visible light conditions and its application. Background Art

[0002] Azobenzene (AB) is an important small organic molecule used as a dye, indicator, and precursor for the synthesis of natural products. Azobenzene is prepared by the catalytic oxidation of the precursor aniline. This catalytic oxidation of the chemically inert aniline molecule requires a proton-assisted multi-electron transfer process and a complex step-by-step oxidation process, which places high demands on the catalyst's catalytic performance.

[0003] Currently, catalysts for aniline oxidation primarily focus on noble metal nanocomposites with extensive surface modification capabilities and structural stability. Most of these catalysts require high catalyst loadings or strong oxidants, and most reported catalytic systems require harsh reaction conditions, such as high pressure and high temperature, to drive the reaction.

[0004] Polyoxometalates (POMs) are crystalline metal oxide clusters with diverse functionalities. They can serve as precursors for the construction of functional POM-based coordination polymers. Coordination polymers are a typical class of crystalline materials with well-defined structures. Certain structural components of these materials confer potential photoresponsive properties. The application of visible-light-driven oxidation of aniline to azobenzene has been largely unexplored. Therefore, coordination polymers with active centers and multi-electron donors are promising alternatives to noble metal catalysts for the catalytic oxidation of aniline to azobenzene. Summary of the Invention

[0005] The technical problem to be solved by the present invention is to provide a polyacid catalyst based on {P4Mo6} crystal state for selective oxidation of aniline under visible light conditions and its application. The catalyst has high activity and stability in selectively catalyzing the oxidation of aniline to azobenzene under visible light drive.

[0006] The technical solution of the present invention is:

[0007] A polyacid catalyst based on {P4Mo6} crystal for selective oxidation of aniline under visible light conditions, the molecular formula of the catalyst is as follows:

[0008] (Hbiz)5{[Co(H2O)3][Co(H2O)2]2}{Co[Mo6O 12 (OH)3(PO4)(HPO4)3][Mo6O 12 (OH)3(PO4)2(HPO4)2]}·3H2O

[0009] Wherein biz is benzimidazole.

[0010] Furthermore, the specific synthesis steps of the polyacid photocatalyst are:

[0011] Na2MoO4·2H2O, benzimidazole, CoCl2·6H2O and H3PO4 were added to an ethanol-water solution in a molar ratio of 2.06:1:0.85:4.24, mixed, and stirred for 0.5 hour, wherein the volume ratio of ethanol to water in the ethanol-water solution was 1:5; then, the pH was adjusted to 1.9 with a 1 mol / L NaOH solution, sealed in a 25 mL polytetrafluoroethylene-lined autoclave, heated in a water bath at 160°C for 4 days, and cooled to room temperature to obtain dark red block crystals, which were washed and dried to obtain a crystalline polyacid catalyst based on {P4Mo6}.

[0012] Furthermore, the molar volume ratio of the Na2MoO4·2H2O to the ethanol aqueous solution is 1.06:3 mol / L.

[0013] A crystalline polyacid catalyst based on {P4Mo6} is used as a selective catalyst for the oxidation of aniline to azobenzene under visible light conditions, exhibiting high catalytic activity, excellent conversion rate, selectivity and cyclic stability.

[0014] A crystalline polyacid catalyst based on {P4Mo6} is used as a selective catalytic catalyst for the oxidation of aniline under visible light conditions. The catalyst is characterized by: selective catalytic oxidation of aniline under 300W xenon lamp illumination at room temperature for 12 hours using the complex as a catalyst, 30% H2O2 as an oxidant, and Na2HSO3 in a mixed solvent of acetonitrile and acetic acid;

[0015] The molar ratio of the complex to 30% H2O2 and Na2HSO3 is 5.0×10 -3 :2.5:0.1;

[0016] The volume ratio of acetonitrile to acetic acid is 7:3;

[0017] The molar volume ratio of the complex to the mixed solvent of acetonitrile and acetic acid is 5.0×10 -3 :3mol / L.

[0018] Furthermore, when the complex is used as a catalyst, 5.0×10 -3 mol catalyst.

[0019] Furthermore, the room temperature is 25°C.

[0020] The beneficial effects of the present invention are:

[0021] (1) The preparation method is simple, the raw materials are readily available and cheap, and no special treatment is required, which greatly reduces time and other energy consumption costs.

[0022] (2) The synthesized {P4Mo6}-based crystalline polyacid catalyst achieves the first catalytic oxidation of aniline derivatives to azo compounds under visible light conditions, without the addition of a photosensitizer. The photocatalytic oxidation of aniline to azobenzene achieves a conversion rate of 97%, with a selectivity for azobenzene of 96%.

[0023] (3) The {P4Mo6}-based crystalline polyacid catalyst has the characteristics of high catalytic activity, structural stability and excellent recyclability. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 is the powder X-ray diffraction spectrum of Example 1 of the present invention;

[0025] Figure 2 is an infrared spectrum of Example 1 of the present invention;

[0026] Figure 3 is the thermogravimetric curve of Example 1 of the present invention;

[0027] Figure 4 is a coordination environment diagram of Example 1 of the present invention;

[0028] Figure 5 is a one-dimensional structural diagram of Example 1 of the present invention;

[0029] Figure 6 is the solid-state UV-Vis diffuse reflectance spectrum of Example 1 of the present invention;

[0030] Figure 7 is the Kubelka-Munk (KM) diagram of Example 1 of the present invention;

[0031] Figure 8 is a Mott-Schottky diagram of Example 1 of the present invention;

[0032] Figure 9 is the photocurrent response curve of Example 1 of the present invention;

[0033] Figure 10 is the cyclic stability of Example 1 of the present invention;

[0034] Figure 11 This is a kinetic study of Example 1 of the present invention;

[0035] Figure 12 1 is the PXRD spectrum before and after the cycle of Example 1 of the present invention. DETAILED DESCRIPTION

[0036] Example 1 Synthesis of (Hbiz)5{[Co(H2O)3][Co(H2O)2]2}{Co[Mo6O 12 (OH)3(PO4)(HPO4)3][Mo6O 12 (OH)3(PO4)2(HPO4)2]}·3H2O

[0037] Na2MoO4·2H2O (0.50 g, 2.06 mmol), benzimidazole (0.118 g, 1 mmol), CoCl2·6H2O (0.20 g, 0.85 mmol), H3PO4 (8 M, 0.53 mL), 1 mL C2H5OH, and 5 mL H2O were mixed and stirred for 0.5 hours. The pH of the mixture was adjusted to 1.9 with 1 M NaOH. The mixture was then sealed in a 25 mL Teflon-lined autoclave and heated at 160°C for 4 days. After cooling to room temperature, dark red blocky crystals were obtained and dried at room temperature to yield a crystalline polyacid catalyst based on {4Mo6}. The yield was 54%.

[0038] 1. Characterization of the {P4Mo6}-based crystalline polyacid catalyst complex (hereinafter referred to as the complex) synthesized in Example 1 of the present invention

[0039] (1) Powder diffraction characterization of phase purity

[0040] Powder X-ray diffraction (PXRD) patterns were recorded using a D / teX superdiffractometer with CuKα radiation, operating at 40 mA and 40 kV. Figure 1 As shown, the powder X-ray diffraction pattern of the complex matches well with the simulated PXRD pattern, indicating that it has high crystallinity and good phase purity.

[0041] (2) Characterization of phase composition by infrared spectroscopy

[0042] The infrared spectrum of the complex was measured on a Varian 640 FT-IR spectrophotometer with a scanning range of 400–4000 cm -1 .like Figure 2 As shown, the infrared spectrum of the complex shows the characteristic vibration of {P4Mo6} polyanion: 1010-1064cm -1 The characteristic peak in the range belongs to the vibration of v(PO), 968cm -1 The characteristic peak at ν(Mo-O t ) vibration, 753cm -1 The frequency range belongs to the vibration of ν(Mo-O-Mo). 1531-1620cm -1The weak absorption bands in the range can be attributed to the vibrations of ν(CH) and ν(CN) in the organic ligands, further confirming the components in the complex structure.

[0043] (3) Thermogravimetric characterization of material stability

[0044] Thermogravimetric analysis was performed using a Hitachi TG / DTA7200 analyzer in a N2 flowing atmosphere with a heating rate of 10°C / min and a temperature range of 25–800°C. Figure 3 As shown, the complex undergoes three weight loss stages in the temperature range of 25 to 800°C. The first weight loss stage at 25–230°C is likely due to the loss of all water molecules. The second and third weight losses from 230 to 800°C are attributed to the thermal decomposition of the organic ligand and polyacid.

[0045] 2. Crystal structure determination

[0046] Diffraction data were collected at 293 K using a Bruker Apex CCD II diffractometer with graphite-monochromated Mo Kα radiation (λ=0.71073 Å). Absorption correction was performed using a multi-scan technique. The structure was solved by direct methods and refined by full-matrix least-squares using the SHELXL program. Figure 4 The coordination environment of the complex synthesized in Example 1 is shown. Figure 5 The one-dimensional structure of the complex is shown. The crystallographic data of the complex are shown in Table 1:

[0047] Table 1 Crystallographic data

[0048]

[0049]

[0050] III. Application of the {P4Mo6}-based crystalline polyacid catalyst complex synthesized in Example 1 of the present invention as a polyacid catalyst for catalytic oxidation of aniline

[0051] In order to evaluate the visible light absorption ability and band structure of the complex, solid-state UV-Vis diffuse reflectance spectroscopy, Mott-Schottky and photocurrent response tests were performed. Figure 6 As shown in Figure 2, the complex exhibits a very broad absorption in the range of 200 nm to 700 nm, indicating its potential as a photocatalyst. In addition, according to the Kubelka-Munk (KM) function ( Figure 7 ), the band gap energy of the complex is about 2.61eV, which means it has the potential to be used as a semiconductor photocatalyst.

[0052] Electrochemical measurements: Mott-Schottky plots and photocurrent-time (i-T) curves were recorded on an electrochemical workstation (CHI-760E, Shanghai, China) using a standard three-electrode system with glassy carbon as the working electrode, a platinum wire as the counter electrode, and an Ag / AgCl electrode as the reference electrode. Indium tantalum oxide (ITO) glass (1 cm × 1.3 cm) was modified with the catalyst sample. 2 mg of crystals were ground into a powder, mixed with 0.99 mL of ethanol and 10 μL of a 0.5% Nafion solution, and sonicated for 60 minutes to form a homogeneous suspension. Subsequently, 200 μL of the suspension was deposited on the ITO glass and dried at room temperature for Mott-Schottky measurements. Mott-Schottky plots were measured at AC frequencies of 500 Hz, 1000 Hz, and 1500 Hz. i-T curves were measured under a 300 W xenon lamp (CEL-LAX 300).

[0053] like Figure 8 As shown in Figure 2, the Mott-Schottky (MS) test at different frequencies found that the conduction band (CB) potential of the complex is approximately -0.97 V relative to Ag / AgCl (-0.77 V relative to NHE). The positive slope of the curve indicates that the complex belongs to an n-type semiconductor material. In addition, the photocurrent response curve ( Figure 9 ) proves that the complex has the ability to photogenerate electrons under visible light excitation. In general, the complex synthesized in the embodiment of the present invention exhibits broad visible light absorption and tunable band structure, and therefore has good application prospects as a photocatalyst.

[0054] The (Hbiz)5{[Co(H2O)3][Co(H2O)2]2}{Co[Mo6O 12 (OH)3(PO4)(H PO4)3][Mo6O 12 The reaction of (OH)3(PO4)2(HPO4)2]}·3H2O as a catalyst for the catalytic oxidation of aniline under visible light conditions was tested. The results showed that the polyacid catalyst constructed based on {P4Mo6} has excellent catalytic activity for the catalytic system and can be used as a photocatalyst to catalyze the oxidation of aniline.

[0055] The process of catalytic oxidation of aniline is as follows:

[0056]

[0057] The present invention conducts photocatalytic oxidation of aniline in a CEL-L870 parallel photoreactor (CEL-LAX300) equipped with a 300W xenon lamp. The reaction system temperature is maintained at 25°C. After the reaction, the aniline oxidation products are identified by GC-MS and quantitatively analyzed using the GC internal standard method.

[0058] The invention uses a complex as a catalyst and selects aniline as a reference substrate to optimize reaction conditions.

[0059] First, under the conditions of catalyst (0.5 mol%), aniline (1.0 mmol), solvent (3.0 mL), NaHSO (0.1 equivalent), 30% H O (2.5 equivalents), and xenon lamp irradiation for 12 hours, the optimal solvent was screened. As shown in Table 2, when polar solvents were used, the reaction efficiency was more significant, especially when acetonitrile was used, the reaction conversion rate could reach 80%. When acetic acid was used as the solvent, although the reaction conversion rate decreased slightly, the selectivity increased to 83%.

[0060] As shown in Table 3, when the volume ratio of acetonitrile to acetic acid is 7:3, it is the best solvent, the conversion rate of the reaction is 84%, and the selectivity of azobenzene can reach 86%.

[0061] Table 2 Effect of solvent on catalytic oxidation of aniline

[0062]

[0063] Table 3 Effect of the ratio of acetonitrile: acetic acid on the catalytic oxidation of aniline

[0064]

[0065]

[0066] To further enhance the catalytic effect, an inorganic salt was used as an additive during the catalytic process. As shown in Table 4, the yield of AB was significantly higher when an inorganic salt containing sulfur atoms was used than when other additives without sulfur atoms were used. The catalytic oxidation effect was even more pronounced when NaHSO (0.1 equivalent) was used.

[0067] Table 4 Effect of additives on catalytic oxidation of aniline

[0068]

[0069] [a] Reaction conditions: catalyst (0.5 mol%), aniline (1.0 mmol), solvent (3.0 ml), NaHSO3 (0.1 equiv), 30% H2O2 (2.5 equiv), xenon lamp, 12 h; [b] Reaction conditions: catalyst (0.5 mol%), aniline (1.0 mmol), solvent (3.0 ml), NaHSO3 (0.05 equiv), 30% H2O2 (2.5 equiv), xenon lamp, 12 h; [c] Reaction conditions: catalyst (0.5 mol%), aniline (1.0 mmol), solvent (3.0 mL), NaHSO3 (0.15 equiv), 30% H2O2 (2.5 equiv), xenon lamp, 12 h; [d] Reaction conditions: aniline (1.0 mmol), solvent (3.0 mL), NaHSO3 (0.1 eq), 30% H2O2 (2.5 eq), xenon lamp, 12 h.

[0070] The present invention rationally evaluates the catalytic activity of each precursor component. As shown in Table 5, when CoCl2, Na2MoO4 and benzimidazole (biz) are used as catalysts, the conversion rate and selectivity of the reaction are low. When these three substances are mechanically ground and mixed, the conversion rate can be increased to 72%, but the selectivity is only 54%, and the catalytic effect is not significantly improved. The results show that the catalyst obtained by simple physical mixing cannot effectively achieve the purpose of promoting the aniline coupling reaction. Therefore, the crystalline catalyst obtained by hydrothermal reaction is effective for this catalytic reaction.

[0071] Table 5 Comparison of the effects of precursor components on aniline oxidation

[0072]

[0073] [a] Reaction conditions: catalyst (0.5 mol%), aniline (1.0 mmol), solvent (3.0 mL), NaHSO3 (0.1 eq), 30% H2O2 (2.5 eq), xenon lamp, 12 h.

[0074] The present invention investigated the effect of time on the catalytic oxidation of aniline using an immobilized catalyst (0.5 mol%), aniline (1.0 mmol), solvent (3.0 mL), 30% H₂O₂ (2.5 equivalents), NaHSO₃ (0.1 equivalents), and a xenon lamp. As shown in Table 6, the catalytic effect of aniline oxidation to azobenzene was optimal when the reaction was run for 12 h.

[0075] Table 6 Effect of time on aniline oxidation

[0076]

[0077] Finally, the effects of environmental factors on the catalytic reaction were explored. As shown in Table 7, when the complex synthesized in Example 1 was used as a catalyst, the catalytic effect under illumination was superior to that without illumination. The catalytic oxidation of aniline not only achieved efficient conversion under xenon lamp irradiation for 12 h, but also achieved a nearly similar azobenzene yield under real sunlight irradiation for 48 h. The selective oxidation of aniline by real solar radiation is very challenging, and therefore the synthesis of the photocatalyst involved in this invention is of great significance for green catalytic organic transformation reactions.

[0078] Table 7 Effects of environmental variables on aniline oxidation

[0079]

[0080] [a] Reaction conditions: catalyst (0.5 mol%), aniline (1.0 mmol), solvent (3.0 mL), NaHSO3 (0.1 eq); [b] 30% H2O2 (2.5 eq), xenon lamp, 12 h; [c] 30% H2O2 (2.5 eq), sunlight, 48 h; [d] 30% H2O2 (2.5 eq), darkness, 48 ​​h.

[0081] As shown in Table 8, the catalytic effect is best under the conditions of catalyst (0.5mol%), aniline (1.0mmol), solvent (3.0mL), NaHSO (0.1 equivalent), 30% H O (2.5 equivalents), and xenon lamp irradiation for 12h. In the absence of catalyst, the reaction is carried out after 12 hours, and the expected product azobenzene and other oxidation products can hardly be obtained, which proves the importance of the catalyst in the catalytic system. When the oxidant is changed to O , the conversion of aniline is only 8%, and when using N to replace H O , the generation of azobenzene is not detected at all. This means that the conversion of aniline and the formation of the target product are closely related to the selection of oxidant, and H O is the best oxidant in this catalytic system.

[0082] Table 8 Deviation of reaction conditions

[0083]

[0084] In summary, the complex synthesized in this invention can effectively catalyze the photocatalytic oxidation of aniline to azobenzene. Optimal catalytic performance was achieved under xenon lamp irradiation for 12 hours using the complex (0.5 mol%) as a catalyst, 30% H₂O₂ (2.5 equivalents) as an oxidant, Na₂HSO₃ (0.1 equivalents) as an additive, and MeCN / AcOH (v / v = 7:3) as a solvent. Aniline conversion reached 97%, and azobenzene selectivity reached 96%.

[0085] The present invention evaluates the application range of the catalyst for the catalytic oxidation of aniline derivatives under optimal reaction conditions. As shown in Table 9, the catalyst has high catalytic activity for the oxidation of aniline derivatives. The catalytic effect of substrates containing electron-withdrawing groups (F and Br) is more significant than that of substrates containing electron-donating groups (Me, Et, iPr, n-Bu and OMe). In addition, studies on the steric effect show that the yield of products substituted with electron-withdrawing groups in the para position is significantly higher than that of products substituted in the ortho and meta positions. It is worth noting that when using compounds containing larger substituents, more than 65% of azobenzene compounds, such as n-butylaniline or isopropylaniline, can still be obtained.

[0086] Table 9 Catalytic oxidation of aniline derivatives

[0087]

[0088]

[0089] Under the optimal conditions, a cycle experiment was conducted on the catalytic oxidation of aniline to evaluate the recyclability and stability of the catalyst. Figure 10 As shown in the figure, after 5 cycles, the catalytic activity remained basically stable, and the yield of azobenzene decreased from 93% to 92%, which was due to a slight loss of catalyst during the recycling process. This shows that the catalyst has excellent cyclic stability. Kinetic studies show that after 5 cycles, the initial reaction rate of aniline did not decrease significantly, which further indicates that it has a certain degree of recyclability ( Figure 11 ).

[0090] After the catalytic reaction, only trace amounts of metal ions are detected in the solution by ICP-MS, which proves the heterogeneity of the catalyst.

[0091] From the infrared spectrum and PXRD pattern of the recovered catalyst ( Figure 12 ) It can be seen that the structure of the catalyst does not change significantly before and after catalysis, further confirming its structural stability and integrity during the reaction.

[0092] The above are merely specific embodiments of the present invention and are not intended to limit the present invention. Those skilled in the art will readily appreciate that the present invention is susceptible to various modifications and variations. Any modifications, equivalent substitutions, or improvements made within the spirit and principles of the present invention shall be included within the scope of protection of the present invention.

Claims

1. A crystalline polyacid catalyst based on {P4Mo6} is used as a selective catalyst for aniline under visible light conditions, characterized in that: The conditions for the selective catalytic oxidation of aniline were as follows: irradiation under a 300 W xenon lamp, at room temperature, with the complex as a catalyst, 30% H2O2 as an oxidant and Na2HSO3 in a mixed solvent of acetonitrile and acetic acid, and irradiation with a xenon lamp for 12 h; The molar ratio of the complex to 30% H2O2 and Na2HSO3 is 5.0×10 -3 :2.5:0.1; The volume ratio of acetonitrile to acetic acid is 7:3; The molar volume ratio of the complex to the mixed solvent of acetonitrile and acetic acid is 5.0×10 -3 :3 mol / L; The molecular formula of the catalyst is as follows: (Hbiz)5{[Co(H2O)3][Co(H2O)2]2}{Co[Mo6O 12 (OH)3(PO4)(HPO4)3][Mo6O 12 (OH)3(PO4)2(HPO4)2]}·3H2O Wherein biz is benzimidazole; The specific synthesis steps of the catalyst are: Na2MoO4·2H2O, benzimidazole, CoCl2·6H2O and H3PO4 were added to an ethanol-water solution in a molar ratio of 2.06:1:0.85:4.24, mixed and stirred for 0.5 hour, wherein the volume ratio of ethanol to water in the ethanol-water solution was 1:5; then, the pH was adjusted to 1.9 with a 1 mol / L NaOH solution, sealed in a 25 mL polytetrafluoroethylene-lined autoclave, heated in a water bath at 160°C for 4 days, cooled to room temperature, and dark red block crystals were obtained. The mixture was washed and dried to obtain a crystalline polyacid catalyst based on {P4Mo6}.

2. The use of the crystalline polyacid catalyst based on {P4Mo6} according to claim 1 as a selective catalytic catalyst for aniline under visible light conditions, characterized in that: The molar volume ratio of the Na2MoO4·2H2O to the ethanol aqueous solution is 1.06:3 mol / L.

3. The use of the crystalline polyacid catalyst based on {P4Mo6} as a selective catalyst in aniline under visible light conditions according to claim 1, characterized in that: When the complex is used as a catalyst, 5.0×10 -3 mol catalyst.

4. The use of the crystalline polyacid catalyst based on {P4Mo6} as a selective catalyst for aniline under visible light conditions according to claim 1, characterized in that: The room temperature is 25°C.

Citation Information

Patent Citations

  • Structure of multi-metal molybdate hybrid compound and preparation method

    CN104277078A

  • Catalytic preparation method of aromatic azoxy compound

    CN113019449A